Further mathematics for economic analysis - Sydsaeter, Knut.; Hammond, Peter; Seierstad, Atle; Strom, Arne (Harlow, England ; New York : Financial Times/Prentice Hall, 2005)
The book is intended for advanced undergraduate and graduate students of economics whose mathematical requirements go beyond the material usually taught in undergraduate courses
Includes bibliographical references (p. [585]-587) and index.
opc 27/09/16
Loans
Keywords: Economics, mathematics; Econometrics; Further mathematics